Chemical modulation of chaperone-mediated autophagy by retinoic acid derivatives - Anguiano, Jaime (2013)
Chaperone-mediated autophagy (CMA) contributes to cellular quality control and the cellular response to stress through the selective degradation of cytosolic proteins in lysosomes. Decrease in CMA activity occurs in aging and in age-related disorders (for example, neurodegenerative diseases and diabetes). Although prevention of this age-dependent decline through genetic manipulation in mouse has proven beneficial, chemical modulation of CMA is not currently possible, due in part to the lack of information on the signaling mechanisms that modulate this pathway. In this work, we report that signaling through the retinoic acid receptor alpha (RARα) inhibits CMA and apply structure-based chemical design to develop synthetic derivatives of all-trans-retinoic acid (ATRA) to specifically neutralize this inhibitory effect. We demonstrate that chemical enhancement of CMA protects cells from oxidative stress and from proteotoxicity, supporting a potential therapeutic opportunity when reduced CMA contributes to cellular dysfunction and disease.